2009
DOI: 10.1038/modpathol.2008.168
|View full text |Cite
|
Sign up to set email alerts
|

BP1, a homeoprotein, is significantly expressed in prostate adenocarcinoma and is concordant with prostatic intraepithelial neoplasia

Abstract: BP1 is a member of the homeobox gene superfamily of transcription factors that are essential for early development. Significant mRNA expression and immunohistochemical reactivity of BP1 is present in a majority of breast cancers and in all cases of inflammatory breast cancer. This study attempts to determine whether BP1 expression is detectable in prostate cancer, another hormone dependent solid tumor, and whether this expression correlates with histopathologic and prognostic factors. Paraffin sections from ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…24,25 For example, overexpression of HOXC6, PAX2, and BP1 have been described in PCa. [26][27][28] We have previously shown that methylation of homeobox genes is a common event in PCa, 14 whereas others have shown similar results in so-called methylation 'hot spots' within HOX loci. 29,30 In particular, we demonstrated methylation of the HOXD3 region in primary PCa and that this methylation leads to gene silencing in DU-145 cells.…”
Section: Discussionmentioning
confidence: 97%
“…24,25 For example, overexpression of HOXC6, PAX2, and BP1 have been described in PCa. [26][27][28] We have previously shown that methylation of homeobox genes is a common event in PCa, 14 whereas others have shown similar results in so-called methylation 'hot spots' within HOX loci. 29,30 In particular, we demonstrated methylation of the HOXD3 region in primary PCa and that this methylation leads to gene silencing in DU-145 cells.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, DLX4 mRNA expression level was an independent prognostic factor for DFS. Schwartz et al suggest that that DLX4 is an important upstream factor in the carcinogenic pathway of prostate cancer and that the expression of DLX4 may reflect or directly contribute to tumor progression and/or invasion [18].…”
Section: Discussionmentioning
confidence: 99%
“…This led to researchers investigating other potential markers to detect prostate cancer at its early stage. Prostate cancer was examined for activation of BP1 [45]. In this study, significant BP1 immunoreactivity was identified in approximately 70% of prostatic tumors, whether the analysis was performed on tissue sections (50 cases) or tissue microarray platforms (123 cases).…”
Section: Prostate Cancermentioning
confidence: 99%